Challenges and opportunities for improving cardiovascular health in women with breast cancer: a review - Ali, Sana; Mullen, Kerri A. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Breast cancer survivors are at a high risk of developing cardiovascular disease (CVD) owing to cancer treatment. Breast cancer and CVD share common risk factors, necessitating CVD risk assessment along with cancer screening. This review aimed to explore the challenges and opportunities associated with promoting cardiovascular health in women with breast cancer. Main text Cardio-oncology is a rapidly developing discipline that focuses on identifying, monitoring, and managing CVD in cancer patients. Preventing and managing CVD in patients with breast cancer involves evaluating risk factors, initiating cardioprotective medications, and implementing cardio-oncology rehabilitation. Major barriers to cardio-oncology prevention and management include inadequate programs, sex/gender-specific issues, financial constraints, underutilization of cardiac rehabilitation (CR), determination of the appropriate time to begin CR, physical limitations, psychological issues, and social and racial disparities. Conclusion A preventive cardio-oncology approach; early identification of cardiotoxicity, CVD risk factors, anxiety, and depression; individualized CR programs; early CR referrals; home/community and virtual CR models; dedicated funding, resources, and personnel; a multidisciplinary team approach; and culturally tailored cardio-oncology care can be beneficial for addressing CVD health challenges and disparities in women with breast cancer.